Thực trạng rèn luyện năng lực chủ nhiệm lớp của sinh viên Trường Đại học Sư phạm Hà Nội 2 dựa trên mô hình học tập trải nghiệm - Trần Thị Loan, Trần Thị Loan (Tạp chí Giáo dục, 2026)
Homeroom teachers serve as a crucial link between families, schools, and society. They are not only responsible for classroom management and maintaining discipline but also act as educators who contribute to students’ holistic development. However, many pre-service teachers continue to face challenges in developing homeroom teacher competencies, especially during their teaching practicum. This study was conducted with 550 third- and fourth-year students from Hanoi Pedagogical University 2 to assess the current status of skill development related to homeroom teacher responsibilities, as well as the relationship between students’ level of interest and their engagement in developing these skills. Using a quantitative research design combined with statistical analysis, the findings reveal that most skills were rated at a fairly good level, though there was noticeable variation among individuals. Based on these results, the study proposes recommendations for universities and teacher education programs to strengthen practice-based activities and experiential learning, thereby creating more effective conditions for students to enhance their homeroom teacher competencies in a substantive and sustainable manner.